Isometric midthigh pull performance is associated with athletic performance and sprinting kinetics in Division I men and women's basketball players: Erratum - Townsend, J. R.; Bender, D.; Vantrease, W. C.; Hudy, J.; Huet, K.; Williamson, C.; Bechke, E.; Serafini, P. R.; Mangine, G. T. (The Journal of Strength and Conditioning Research, 2020)
In the October 2019 issue of the Journal of Strength and Conditioning Research in the manuscript by Townsend et al. (1), an error was made in the initial submission of this article in reference to the hang clean data in Table 1. The following table has the correct values for the hang clean data.